Analisis Pengaruh Implementasi Teori Vygotsky Terhadap Pembelajaran Di Kelas - Ardania, Nabila; Mafaza, Fiki Mahya; Jannah , Imatriya Nur; Putri, Annisa Eka; Arochman, Taufik (Indonesian Journal of Education and Learning, 2024)
Vygostky's learning theory discussed in this article was pioneered by a figure named Lev Vygotsky who argued that learning is a social process. According to him, children have expertise in developing knowledge starting from social interactions with their social environment. One of the applications is cooperative learning conducted in a group, which contains a group of children who have different abilities to work together and help each other. Vygotsky's theory has the advantage that students are able to think together in solving problems so that the problem can be solved, but it also has the disadvantage that the time needed is longer because of the different abilities of students. The writing of this article aims to find out the history of the Vygotsky theorist, the concept of Vygotsky theory, the implementation of Vygotsky theory in education and its influence in learning. The author uses literature review and questionnaire methods in writing this article. The results obtained from this study were that some of the respondents felt helped by the implementation of Vygotsky's theory in learning, while others did not feel helped or neutral.